2012
DOI: 10.1007/s00431-012-1701-0
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and overweight/obesity in adults: a meta-analysis

Abstract: Neither positively linear nor J- or U-shaped relations exist between birth weight and overweight/obesity in adults. It is high birth weight, not low birth weight, that is associated with increased risk of overweight/obesity in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 29 publications
8
78
1
3
Order By: Relevance
“…A systematic review and meta-analysis showed that high birth weight (>4,000 g) is associated with an increased risk of obesity [27]. Other studies also confirmed that high birth weight contributes to later childhood obesity [7, 24, 26, 28, 29] and to increased body fat mass [23]. Low birth weight (<2,500 g) occurs due to inadequate intrauterine conditions that lead to abnormal fetal development, and although the influence of low birth weight on the development of obesity is still not so clear [27], it has been associated with lower lean body mass and greater central adiposity, measured by the waist-to-hip ratio or skinfold thickness in adults [30, 31].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A systematic review and meta-analysis showed that high birth weight (>4,000 g) is associated with an increased risk of obesity [27]. Other studies also confirmed that high birth weight contributes to later childhood obesity [7, 24, 26, 28, 29] and to increased body fat mass [23]. Low birth weight (<2,500 g) occurs due to inadequate intrauterine conditions that lead to abnormal fetal development, and although the influence of low birth weight on the development of obesity is still not so clear [27], it has been associated with lower lean body mass and greater central adiposity, measured by the waist-to-hip ratio or skinfold thickness in adults [30, 31].…”
Section: Introductionmentioning
confidence: 85%
“…The relationship between high birth weight and later obesity might be explained by disturbances during critical periods of development (such as intrauterine growth and infancy), which may cause permanent metabolic, physiological and structural adaptations [29]. Other related factors include gestational overnutrition, maternal diabetes mellitus, maternal obesity, excessive maternal weight gain and prolonged gestation, which increase the risk of later obesity [28, 58] and have also been related to premature delivery. In a study which included more than 1 million women from 84 studies [59], analysis confirmed that overweight and obese women had a higher risk of delivering prior to 32 weeks of gestation and had a higher risk of induced delivery before 37 weeks; also, being overweight or obese was associated with a 30% increased risk of early delivery [59].…”
Section: Discussionmentioning
confidence: 99%
“…HBW, exposure to GDM, and childhood obesity are associated with an increased risk of obesity in later life, although the effect on hypertension seems variable (Box 2). 18,143,144 Early childhood nutritional status is therefore also crucial in determining the risk of disease for an individual during the course of their lifetime.…”
Section: Obstruction Of the Developing Kidneymentioning
confidence: 99%
“…However, due to the continuous increase, in the last two decades, of mean birth weight in several countries worldwide [9,10], it is expected that higher birth weight will play a more important role as a risk factor for further obesity [5,11,12] than low birth weight.…”
Section: Introductionmentioning
confidence: 99%